1980
DOI: 10.1038/icb.1980.63
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Histology of Two Xo Murid Rodents From Australia

Abstract: Summary. Single XO individuals of Rallu.s liinneyi and Mesemhriomys (Rodentia: Muridae) proved to be phenolypic females. Comparisons of the ovaries of these mdividuals with XX controls revealed that the R nmncyi washistologically nonnal. whereas the M. goiildii was histologicaliy unusual. The results are discussed in relation to the Lyon and Hawker hypothesis which relates fertility of XO mammals to shortness of life-span. INTRODUCTIONIn mammals, the Y-chromosome is male-determining so that XO individuals are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…G-banding showed that these individuals, both of which were female, possessed a full complement of autosomes, but only a single X-chromosome and no Y-chromosome. The G-banded karyotype and ovarian histology of one such individual has been published elsewhere (Baverstock et al, 1980).…”
Section: Variantsmentioning
confidence: 99%
“…G-banding showed that these individuals, both of which were female, possessed a full complement of autosomes, but only a single X-chromosome and no Y-chromosome. The G-banded karyotype and ovarian histology of one such individual has been published elsewhere (Baverstock et al, 1980).…”
Section: Variantsmentioning
confidence: 99%